2009
DOI: 10.1016/j.evalprogplan.2009.05.001
|View full text |Cite
|
Sign up to set email alerts
|

A mixed methods evaluation of televised health promotion advertisements targeted at older adults

Abstract: The purpose of this research was to evaluate television advertisements targeted at 55-70-year olds that promoted physical activity and fruit and vegetable consumption. Awareness of the campaign, perceived credibility of the source, intentions to visit a promoted website, and intentions to perform the healthy behaviors were evaluated using mixed methods research. Results from a population level survey (n = 1600) showed low unprompted and prompted awareness of the campaign and no differences in intentions or beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 27 publications
3
24
0
Order By: Relevance
“…Confusion between multiple programmes, activities and messaging has been noted in other studies (16,39,40) . In addition, there was some unavoidable contamination of the New England control area with some of the programme strategies such as Fruit 'n' Veg month that occurred across the state.…”
Section: Limitationssupporting
confidence: 54%
“…Confusion between multiple programmes, activities and messaging has been noted in other studies (16,39,40) . In addition, there was some unavoidable contamination of the New England control area with some of the programme strategies such as Fruit 'n' Veg month that occurred across the state.…”
Section: Limitationssupporting
confidence: 54%
“…The studies 170,179 found that recall of a Canadian and an Australian mass media campaign, respectively, was very poor. An advertisement that formed part of the Canadian campaign featured the grim reaper as a warning of what might happen if a healthy lifestyle was not taken up.…”
Section: 179mentioning
confidence: 99%
“…Use of websites as further sources of information were criticised because not everyone has a computer or access to the internet. 179 Participants reporting on the Australian campaign suggested that health promotion messages should not be broadcast on television during the advertisement break as people tend not to view at those times. The recommendations to walk on most days were not perceived by the participants as being strong enough, with most people already carrying out that amount of activity.…”
Section: 179mentioning
confidence: 99%
See 2 more Smart Citations